Targeted differential photostimulation alters reproductive activities of domestic birds - Rozenboim, I.; Bartman, J.; Avital Cohen, N.; Mobarkey, N.; Zaguri, S.; El Halawani, M. E.; Chaiseha, Y.; Marco, A. (Frontiers in Physiology, 2022)
Modern poultry production systems use environmentally controlled houses providing only artificial illumination. The role of light in reproduction of poultry depends on light quality (photoperiod, intensity/brightness, and spectrum), which enables us to provide custom-made illumination, targeted for the elevation of reproductive activities. Artificial targeted illumination significantly affects poultry reproduction. This phenomenon is based on the mechanism of light absorption in birds, which consists of two main components: the eye (retinal photoreceptors) and brain extraretinal photoreceptors. Several experiments on turkey hens and broiler breeder males and females have shown that photostimulation of brain extraretinal photoreceptors, while maintaining retinal photoreceptors under non-photostimulatory conditions, elevates reproductive activity by increasing egg production of hens and semen quality of roosters. In addition, we found acceleration in all gonadal axis parameters, leading to the acceleration in the production rate. Furthermore, we studied the role of retinal activation in gonadal axis suppuration and identified the role of serotonin in this phenomenon. As for today, several broiler breeder farms use targeted illumination based on our studies with excellent results.